Comments on the applicability of "An improved weighted recursive PCA algorithm for adaptive fault detection". (January 2017) - Quiñones-Grueiro, Marcos; Verde, Cristina
Abstract: This paper discusses some limitations of the weighted recursive PCA algorithm (WARP) proposed by Portnoy, Melendez, Pinzon, and Sanjuan (2016) which is used for fault detection (FD) by arguing that it can reduce false alarms. The motivation of these comments is the lack of a clear criterion in the WARP algorithm to distinguish between process deviations and faults' scenarios, and as a consequence, the applicability of this algorithm is questionable from the FD point of view. Moreover, we address the absence of a formal justification why the computational complexity achieved by using the WARP algorithm is reduced in comparison with methods discussed in the paper. Abstract : Highlights: Applicability of the weighted recursive PCA (WARP) algorithm. Limitations of the WARP algorithm from fault detection point of view. Issue to distinguish between faults and normal operation variations.